Obstacles to achieve the SDGS in El Salvador. Youth policies, young gangs and NGOs: a complex analysis - Navarro-Pérez, José Javier; Martínez-Reyes, Alberto (Iberoamerican Journal of Development Studies, 2020)
In this qualitative study, based on semi-structured interviews with experts from non-governmental organizations and life stories with young gang members, it is analyzed the incidence of youth gangs in the Development Agenda in El Salvador and it is identified the risk factors of policies aimed at youth. The main results exhibit how youth gangs, violence and failed public policies have limited the achievement of development goals. Regarding these findings, a series of proposals are presented to reduce violence and its impact on civil society, relying on non-governmental organizations and on the strengthening of institutions and democracy.